Redesain pendidikan islam: perkembangan pendidikan pasca penerapan syari’at islam di aceh - Abidin Nurdin; Sri Astuti A. Samad; Munawwarah Munawwarah (Institut Agama Islam Negeri (IAIN) Bone, 2020)
This study aims to discuss the redesign of Islamic education which is focused on the development of Islamic education after the Islamic shari'ah was formally applied in Aceh. As it is understood that the application of Islamic sharia is a part of the historical mandate, and has become a characteristic of the social and cultural order of the Acehnese people which is thick with religious values, the latter is then strengthened by law regulations from the central government. The method used is qualitative research with data collection techniques namely literature review, interviews and observations while the analysis technique uses tryangulation. The result is that since the implementation of Islamic sharia in Aceh there has been a redesign of Islamic education, which is to strengthen the three centers of education which are also based and synergized with Islamic sharia. The three education centers are: first, the (formal) school from elementary school but up to tertiary institutions; secondly, the community (non-formal), at the level of the village where there is a meunasah and the study center as a place of study of tauhid, fiqih and tasawuf; and third, family (informal) through family strengthening. Thus the tri education center is enriched with Islamic sharia values that shape human character and noble character.Kajian ini bertujuan untuk membahas tentang redesain pendidikan Islam yang difokuskan pada perkembangan pendidikan Islam setelah syari’at Islam diterapkan secara formal di Aceh. Sebagaimana dipahami bahwa penerapan syari’at Islam merupakan bagian dari amanah sejarah, dan telah menjadi karaktersitik tatanan sosial dan budaya masyarakat Aceh yang kental dengan nilai-nilai agama, terakhir kemudian diperkuat dengan peraturan udang-undang dari pemerintah pusat. Metode yang digunakan adalah penelitian kualitatif dengan teknik pengumpulan data yaitu kajian literatur, wawancara dan observasi sedangkan teknik analisis memakai tryangulasi. Hasilnya adalah bahwa sejak penerapan syari’at Islam di Aceh terjadi redesain pendidikan Islam yaitu menguatkan tiga pusat pendidikan juga berbasis dan bersinergis dengan syar’at Islam. Tri pusat pendidikan tersebut yaitu: pertama, sekolah (formal) dari Sekolah Dasar tetapi sampai pada Perguruan Tinggi; kedua, masyarakat (non formal), pada level gampong yang terdapat meunasah dan balai pengajian sebagai tempat pengkajian ilmu tauhid, fiqih dan tasawuf; dan ketiga, keluarga (informal) melalui penguatan keluarga. Dengan demikian tri pusat pendidikan tersebut diperkaya dengan nilai-nilai syari’at Islam yang membentuk manusia berkarakter dan berakhlak mulia.